Outcomes and Healthcare Utilization Among New Persistent Opioid Users and Nonopioid Users After Curative-intent Surgery for Cancer. Issue 4 (29th April 2023) - Lin, Na; Dabas, Eashita; Quan, May Lynn; Cheung, Winson Y.; Cuthbert, Colleen; Feng, Yuanchao; Kong, Shiying; Sauro, Khara M.; Brenner, Darren R.; Yang, Lin; Lu, Mingshan; Xu, Yuan
Abstract : Objective: The aim of the study was to compare the health outcomes and resource use of cancer patients who were new persistent opioid users with those who were not, after undergoing curative intent surgery for cancer. Background: Little is known about long-term health outcomes (overdose, mortality) and resource utilization of new persistent opioid users among cancer patients undergoing curative-intent surgery. Methods: This retrospective cohort study included all adults with a diagnosis of solid cancers who underwent curative-intent surgery during the study period (2011–2015) in Alberta, Canada and were opioid-naïve before surgery, with a follow-up period until December 31, 2019. The key exposure, "new persistent opioid user, " was defined as a patient who was opioid-naive before surgery and subsequently filled at least 1 opioid prescription between 60 and 180 days after surgery. The primary outcome was opioid overdose that occurred within 3 years of surgery. All-cause death, noncancer caused death, and department visit (yes vs. no), and hospitalization (yes vs. no) in the follow-up periods were also included as outcomes. Results: In total, 19, 219 patients underwent curative intent surgery with a median follow-up of 47 months, of whom 1530 (8.0%) were identified as postoperative new persistent opioid users. In total, 101 (0.5%) patients experienced opioid overdose within 3 years of surgery. Compared with nonopioid users, new persistent opioid users experienced a higher rate of opioid overdose (OR = 2.37, 95% CI: 1.44–3.9) within 3 years of surgery. New persistent opioid use was also associated with a greater likelihood of being hospitalized (OR = 2.03, 95% CI: 1.76–2.33) and visiting an emergency room (OR = 1.83, 95% CI: 1.62–2.06) in the first year after surgery, and a higher overall (HR = 1.28, 95% CI: 1.1–1.49) and noncancer caused mortality (HR = 1.33, 95% CI: 1.12–1.58), when compared with nonopioid users. Conclusion: Postoperative new persistent opioid use among cancer patients undergoing curative-intent surgery is associated with subsequent opioid overdose, worse survival, and more health resource utilization.